A correctional orientation of psychological-pedagogical support of sports activity sportsmen high qualification in sports of disables. - Boyko G.M (Kharkov National Pedagogical University, 2010)
Correction terms are grounded, base maintenance of the system is developed psychological-pedagogical accompaniments of sporting activity of invalids. On the problems of sport of invalids over 100 literary sources are analysed. It is set that the observance of correction terms foresees the high degree of individualization of planning and realization of the special measures of psychological preparation. It is marked that correction terms must answer the structure of competition activity of sportsmen. An accent is done on the necessity of clear regulation and coordination of professional actions of specialists during work with sportsmen.